2005
DOI: 10.1074/jbc.m505367200
|View full text |Cite
|
Sign up to set email alerts
|

Processing of Viral DNA Ends Channels the HIV-1 Integration Reaction to Concerted Integration*[boxs]

Abstract: Retroviral DNA made by reverse transcription is blunt-ended, and the viral integrase protein must remove two nucleotides from each 3 end prior to integration into chromosomal DNA. Under most reaction conditions for integration in vitro, the majority of the reaction products are "half-site" products that result from integration of only one viral DNA end into one strand of the target DNA. Preprocessed DNA substrates are more efficient substrates for half-site reactions than are blunt-ended substrates, which requ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
127
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(136 citation statements)
references
References 48 publications
9
127
0
Order By: Relevance
“…2. This essential aspect of the in vivo reaction has typically been difficult to recapitulate in vitro with the purified enzyme, although recent adjustments to assay parameters have boosted efficiency [155,156]. The effect of p75 differed sharply between different recombinant lentiviral IN proteins: its addition enhanced full-site integration for EIAV IN while HIV IN was instead directed virtually exclusively to catalyze uncoupled (half-site) integration in which only one viral DNA end is joined to one strand of target DNA [100].…”
Section: Modeling P75 Function In the Hiv Life Cyclementioning
confidence: 99%
“…2. This essential aspect of the in vivo reaction has typically been difficult to recapitulate in vitro with the purified enzyme, although recent adjustments to assay parameters have boosted efficiency [155,156]. The effect of p75 differed sharply between different recombinant lentiviral IN proteins: its addition enhanced full-site integration for EIAV IN while HIV IN was instead directed virtually exclusively to catalyze uncoupled (half-site) integration in which only one viral DNA end is joined to one strand of target DNA [100].…”
Section: Modeling P75 Function In the Hiv Life Cyclementioning
confidence: 99%
“…Complementation studies with two defective forms of HIV-1 IN revealed that subunits can multimerize to become active (38,39). Recent studies indicate that the IN of HIV-1 is a tetramer in its synaptic complex and that multimerization of the C-terminal domain plays an important role in concerted integration (7,40). Our results of gel filtration indicated that full-length Tf1 IN formed a stable dimer.…”
Section: Discussionmentioning
confidence: 57%
“…The HIV IN monomer purified in the presence of EDTA is converted into a tetramer in the presence of Zn 2+ without the formation of a dimer intermediate [53,54] . Studies have demonstrated that a tetramer of IN is associated with HIV, PFV and RSV SC capable of concerted integration [50,[55][56][57] . The oligomeric state of retrovirus IN play key roles in virus maturation upon release of the virus particle, enzymatic activities for 3' OH processing and concerted integration of viral DNA and possibly for reverse transcription in the cytoplasmic PIC.…”
Section: Solution Properties Of Inmentioning
confidence: 99%